2008
DOI: 10.1093/schbul/sbn064
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-Methyltransferase Val158Met Polymorphism and Antisaccade Eye Movements in Schizophrenia

Abstract: The catechol-O-methyltransferase (COMT) enzyme catabolizes dopamine. The val(158)met single nucleotide polymorphism (rs4680) in the COMT gene has received considerable attention as a candidate gene for schizophrenia as well as for frontally mediated cognitive functions. Antisaccade performance is a good measure of frontal lobe integrity. Deficits on the task are considered a trait marker for schizophrenia. The aim of this study was to investigate the association of COMT val(158)met polymorphism with antisaccad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 78 publications
2
29
0
Order By: Relevance
“…48 Other genes have been found to be associated with AS performance, including the gene encoding the regulator of G-protein signaling subtype 4 ( RGS4 ) 119 and COMT. 120 However, the pedigree-based COGS study did not find these effects. 48 …”
Section: Antisaccade Taskmentioning
confidence: 95%
“…48 Other genes have been found to be associated with AS performance, including the gene encoding the regulator of G-protein signaling subtype 4 ( RGS4 ) 119 and COMT. 120 However, the pedigree-based COGS study did not find these effects. 48 …”
Section: Antisaccade Taskmentioning
confidence: 95%
“…One of the primary reasons that EMD has been of such interest is that several lines of evidence converge in support of a genetic influence on EMD, thereby implying that EMD will assist in gene identification. Indeed, a small number of molecular genetics studies have provided promising preliminary evidence in support of a relationship between EMD and particular genes (Ettinger et al, 2008; Haraldsson et al, 2008; Rybakowski & Borkowska, 2002; Rybakowski, Borkowska, Czerski, & Hauser, 2001; Thaker, Wonodi, Avila, Hong, & Stine, 2004) or chromosomal regions (Arolt et al, 1996; Arolt et al, 1999; Matthysse et al, 2004; Myles-Worsley et al, 1999). While these studies are important in their attempts to investigate the genetic underpinnings of EMD, they are few, difficult to replicate, typically employ small samples, cover few of the different forms of EMD that have been implicated in schizophrenia, and give us little to go on when faced with how to evaluate the candidacy of different aspects of EMD as endophenotypes.…”
mentioning
confidence: 99%
“…Thaker et al (2004) showed an advantage in predictive pursuit for healthy Met allele homozygotes and found 10% of variance in the gain parameter to be explained by the COMT genotype. In contrast, Haraldsson et al (2010) failed to find a significant association in a similar study. However, they measured pursuit on continuous waveform motion without target blanking, so extraretinal processes might have been insufficiently prominent.…”
Section: Discussionmentioning
confidence: 76%
“…Some findings point to functional associations with antisaccade performance (Ettinger et al, 2008; Haraldsson et al, 2010; Kasparbauer et al, 2015), but differences foremost showed up in BOLD responses. Smooth pursuit seems ideal for studying different mechanisms involved in oculomotor control, because it relies on a sophisticated interplay between motion perception, sensorimotor transformation, and anticipatory abilities (Lisberger, 2010; Kowler et al, 2014).…”
Section: Introductionmentioning
confidence: 98%